Peran Musik sebagai Terapi Jiwa bagi orang yang Berduka Menurut I Samuel 16: 14-23 dan Relevansinya dalam konteks Kristen Batak - Sinaga, Elperida; Purba, Armila; Damanik, Riecha Priyadi Fhany (Sekolah Tinggi Diakones HKBP, 2025)
Music has the ability to touch the emotional, psychological, and spiritual dimensions of human life. From a biblical perspective, music functions not only as a part of worship but also as a means of spiritual healing, as seen in the story of David playing the harp to soothe King Saul's mental illness (1 Samuel 16:14–23). In the Batak cultural context, traditional music such as gondang, tortor, and ende also has a strong spiritual function as a medium for prayer, comfort, and emotional healing, building solidarity and community strength. This study uses a qualitative approach through literature review to examine the role of music as spiritual therapy based on biblical examples and its relevance in Batak tradition. The results show that music plays not only a theological role but also an important pastoral tool in the lives of the Batak people. Therefore, the church needs to develop contextual music services that are able to address the emotional and spiritual needs of the contemporary Batak congregation.